ОСОБЕННОСТИ СЛОВООБРАЗОВАТЕЛЬНОЙ КОНЦЕПТУАЛИЗАЦИИ И КОНЦЕПТА СОВРЕМЕННОЙ ЛИНГВИСТИКИ - Елмуратова, С.А. (SCIENCE and SOCIETY, 2024)
The article presents theories of the conceptual nature of word-formation meanings; word-formation categories are considered as structures for representing knowledge, organized in accordance with the grammatical system of the Russian language.